Deconfined criticality from the QED3-Gross-Neveu model at three loops - Ihrig, Bernhard; Janssen, Lukas; Mihaila, Luminita; Scherer, Michael (Physical review, 2018)
The QED3-Gross-Neveu model is a (2+1)-dimensional U(1) gauge theory involving Dirac fermions and a critical real scalar field. This theory has recently been argued to represent a dual description of the deconfined quantum critical point between Néel and valence bond solid orders in frustrated quantum magnets. We study the critical behavior of the QED3-Gross-Neveu model by means of an ε expansion around the upper critical space-time dimension of D+c=4 up to the three-loop order. Estimates for critical exponents in 2+1 dimensions are obtained by evaluating the different Padé approximants of their series expansion in ε. We find that these estimates, within the spread of the Padé approximants, satisfy a nontrivial scaling relation, which follows from the emergent SO(5) symmetry implied by the duality conjecture. We also construct explicit evidence for the equivalence between the QED3-Gross-Neveu model and a corresponding critical four-fermion gauge theory that was previously studied within the 1/N expansion in space-time dimensions 2<D<4.
Im Titel ist die Zahl "3" tiefgestellt
Gesehen am 23.01.2020